PENGARUH GAYA HIDUP DAN MOTIVASI KONSUMEN TERHADAP KEPUTUSAN PEMBELIAN PRODUK LAPTOP ASUS (Studi Pada Mahasiswa Prodi D4 Manajemen Pemasaran Jurusan AdministrasiNiaga Politeknik Negeri Malang) - Ayla Nadratul Widad; Asminah Rachmi (ADISAM PUBLISHER, 2025)
The results of technology are widely used by young people to the elderly. This can be seen from the increasing popularity of laptop products, one of which is Asus Laptops. The Asus laptop company provides the choices consumers need according to consumer lifestyles and motivations. This research aims to determine the influence of consumer lifestyle and motivation on purchasing decisions for Asus laptop products. This research is quantitative research. The data collection method used was distributing questionnaires to 65 respondents using random sampling techniques. Data analysis uses multiple regression analysis and hypothesis testing. The research results show that based on the t (partial) hypothesis test, consumer lifestyle and motivation variables partially have a positive and significant effect on purchasing decisions. The results of the hypothesis test F (simultaneous) explain that lifestyle variables and consumer motivation simultaneously (together) have a positive influence on purchasing decisions. From the results of this research, it is hoped that the Asus Laptop company will pay more attention to the role of consumer lifestyle and motivation factors, in order to improve purchasing decisions for Asus laptop products